Pengembangan Modul Pembelajaran Perawatan Berkala Sistem Pendingin Air Pemeliharaan Mesin Sepeda Motor - Rahmiati Ruwaida; Abubakar Dabet; Siraj; Taufiq (Jurnal Multidisiplin Madani, 2022)
Module development is one of the efforts to increase students' independence in learning. Research objectives: (1) module development; (2) module feasibility; (3) student learning outcomes on the material for periodic maintenance of the water cooling system. The type of research is Research and Development. The instruments used were observation, interviews, questionnaires, and documentation. Data analysis techniques include: media and material expert validation, percentage qualitative analysis, and t-test analysis. The results of the study show that: (1) module development makes students more active and learn independently, 2) validation results from module development are very suitable, obtained material expert validation values of 94.16% and 95.55%, and validation values from experts media by 93.78% and 92.42%. 3) student learning outcomes have increased as evidenced by the score obtained by the experimental class of 94.6%.